The Exquisite Sophistication of French Scholarly Writing: French Spirit or French Letter? - Colson, Jacques (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractOne salient feature of contemporary French scholarly writing is its high degree of stylistic sophistication, which does not seem to be present in English. This paper examines the validity of this observation by attempting a definition of scholarly writing common to English and French, and by characterizing and comparing stylistic sophistication in both languages. Typical texts and their translations are then examined, which confirm the hypothesis, and sociolinguistic explanations are suggested to account for it.